Dikotomi dan Integrasi: Studi Komparatif Epistemologi Ilmu Pengetahuan dalam Tradisi Barat dan Islam - Sumiran, Sumiran; Aidil, Muhammad; Jumingan, Jumingan (Lembaga Yasin AlSys, 2026)
Epistemology is a fundamental foundation that guides the development of civilization through knowledge, yet Western and Islamic traditions have developed epistemological bases that differ in essential ways. This paper aims to provide an in-depth analysis of the differences between Western and Islamic epistemology and their implications for the development of knowledge. Using a descriptive-analytical method and a comparative approach to relevant philosophical sources, the study shows that Western civilization positions rationalism and empiricism as the primary, anthropocentric sources of truth, thereby contributing to the secularization of knowledge. In contrast, Islamic epistemology presents a theocentric paradigm that integrates revelation (wahyu) as the primary source of knowledge, supported by reason (‘aql), the senses (hissī), and intuition (‘irfānī) within a unified hierarchical order. These differing epistemological foundations influence not only how research methods are formulated but also the value orientation, ethics, and ultimate goals of knowledge development. The findings affirm the importance of integrating knowledge by synthesizing rational–empirical strengths with spiritual depth grounded in revelation as an effort to respond to the crises of objectivity and spirituality in modern science and to reorient knowledge toward the holistic well-being of humankind.